Multiband modulation spectroscopy for the determination of sex and species of mosquitoes in flight. Issue 8 (16th April 2018) - Gebru, Alem; Jansson, Samuel; Ignell, Rickard; Kirkeby, Carsten; Prangsma, Jord C.; Brydegaard, Mikkel
Abstract : We present a dual‐wavelength polarimetric measurement method to distinguish species and sexes of disease transmitting mosquitoes in flight. By measuring co‐ and de‐polarized backscattered light at 808 and 1550 nm, the degree of linear polarization, wingbeat frequency, reflectance, spectral ratio and glossiness of mosquitoes can be retrieved. Body and wing contributions to these signals can be separated. Whereas the optical cross section is sensitive to the aspect of observation, thus the heading direction of the insect in flight, we demonstrate that polarimetric‐ and spectral‐band ratios are largely invariant to the aspect of observation. We show that wing glossiness, as well as wing‐ and body‐spectral ratios are particularly efficient in distinguishing Anopheles coluzzii and Anopheles arabiensis, 2 closely related species of malaria vectors. Spectral and polarimetric ratios relate to microstructural and melanization features of the wing and body of these species. We conclude that multiband modulation spectroscopy is a useful expansion of the parameter space that can be used to improve the specificity of entomological lidars. Abstract : Four disease‐carrying mosquito species are investigated with a dual‐band polarimetric instrument. We report on cross sections for both the insect body and the oscillatory wing component and interpret the results. We find several aspect invariance parameters and contrast for species and sex. We demonstrate benefits for multiple bands. The promising results pave the way for target classification in entomological lidar.